STRATEGIC TASKS BEING IMPLEMENTED IN THE FIELD OF GEOGRAPHY EDUCATION IN NEW UZBEKISTAN (International journal of artificial intelligence, 2026)
This article discusses the strategic reforms being implemented in the field of geography education in New Uzbekistan, their content and significance. It also analyzes the issues of introducing modern pedagogical technologies into the educational process, improving the skills of teachers, developing practical training, and forming an ecological culture. The article provides a conclusion about the future prospects of geography education and its role in the development of society.